HUBUNGAN PEMAKAIAN KB SUNTIK 3 BULAN DENGAN PERUBAHAN SIKLUS MENSTRUASI DI BPM ANIK DESA SIDODADI: The Correlation Between Use of 3-Month Injectable Family Planning and Changes in The Menstrual Cycle at Anik Independent Midwife Practice, Sidodadi Village - Dwi Astuti (Forind Press, 2023)
Injectable contraception is a type of hormonal birth control that contains estrogen and progesterone preparations which have several impacts that are most complained about by injecting birth control acceptors, namely changes in the menstrual cycle. The purpose of this study was to analyze the correlation between acceptors of 3-month family planning injections who experienced changes in the menstrual cycle at Anik independent midwife practice in Sidodadi. The research design was an analytic survey with a cross sectional approach. The population of this study were all women of childbearing age who used the 3-month injection at Anik independent midwife practice in Sidodadi totaling 50 people. The data used are primary and secondary data. The instrument used is a questionnaire. Univariate and bivariate data analysis techniques. Data were analyzed by conducting Chi-square test analysis. The results of the study from 50 respondents who experienced regular menstrual cycles were 13 people (26%), who experienced irregular menstrual cycles were 37 people (74%). The result of the chi-square test is p-value = 0.000. The conclusion in this study is that there is a relationship between the use of 3-month injections and the menstrual cycle at Anik independent midwife practice. It is recommended that midwives provide counseling and counseling to new acceptors regarding the side effects and risks that occur with the use of 3-month injectable birth control.